Effect of Dosage of Alkaline Activator on the Properties of Alkali-Activated Slag Pastes - Zhenzhen Jiao; Ying Wang; Wenzhong Zheng; Wenxuan Huang (Advances in Materials Science and Engineering)
This study focused on the engineering properties of alkali-activated slag (AAS) pastes prepared by mixing an activator consisting of sodium silicate and sodium hydroxide at room temperature. The water-to-slag ratio of AAS paste was kept constant at 0.35 by mass. AAS pastes were prepared using the activator with five different silicate moduli of 1, 1.2, 1.4, 1.6, and 1.8 and three different Na2O contents of 6%, 8%, and 10%. The results showed that both the silicate moduli and Na2O contents had significant effects on the engineering properties of AAS pastes. All the AAS pastes exhibited properties such as fast setting, good workability, and high early compressive strength. The final setting time varied from 9 to 36 min, and the fluidity was in the range of 147–226 mm. The 1 d compressive strength of all the AAS pastes, which could be easily achieved, had values above 55 MPa, whereas the highest strength obtained was 102 MPa with the silicate modulus of 1 and Na2O content of 8% at room temperature. The drying shrinkage increased as the silicate modulus increased. Furthermore, the hydration products and microstructures of AAS pastes were explained according to the microanalysis methods.